Analisis Pergeseran Otoritas Guru dalam Perspektif Teori Kekuasaan Michel Foucault pada Platform Tiktok - Nuridilah Sidra; Hadisaputra; Reni Anggraeni; Nurul Annisa; Haikal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the phenomenon of teacher reporting to the legal sphere that is developing through TikTok social media and its implications for the shift in teacher authority in the 21st century. The study uses a descriptive qualitative approach with a case study method through digital documentation analysis, media observation, and literature review related to education, law, and Michel Foucault's Surveillance/Panopticon theory. Data in the form of video content, news narratives, and public responses are analyzed through data reduction, data presentation, and drawing conclusions. The results of this study indicate that cases of teacher reporting form a modern oversight mechanism that places teachers in a position of constant scrutiny by the public, the law, and social media. This condition indicates a shift in teacher authority. Teacher disciplinary actions are easily interpreted by the public as violations of the law and will affect the professional image of teachers. This study emphasizes the need for legal protection, educational discipline policies, and the reconstruction of public trust to maintain teacher authority without neglecting children's rights.